(3JGL GdYQhS aj TQM GdbGehSs - (3eMeO Hf eMeO Hf eMeO Hf YHO GdQGRb, GdSjO eQJVj GdMSjfj GdRHjOj,CHh GdajV , J (B1205 (3g` s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3HGH GdgGA ef cJGH GdbGehS (B: (3hGdgGA ef GdMQha GdMdbjI , hgj GdYjf hGdMGA hGdgGA hGdNGA hGdZjf , hgj CjVG ef GdMQha GdegehSI hgj GdgGA hGdMGA hGdNGA hGdcGa s
(3BNQgG (B:s
(3hjfSd Edi GdQHG Ydi daXg ajbGd QHhi , bGd CHh YHjOI hRGO GdeWQRi abGd GdaJM ai GdfSHI NWC hCQHi GdQLd ONd ai GdQHG hLeY GdQHhI HGdVje QHi ceOjI heOi GdQHhehVY s
(3GdLRA GdJGSY hgh GdCNjQ hHg MQa GdgGA hGdhGh hGdjGAs
(3Ydi ghGeTgG EVGaGJ hJUMjMGJ HNW GdeDdas
(3GdfSNI HgG MhGTs
(3HOGNdgG Cfg CJe MQa GdgGA SfI (B1187(3g` s
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs